First Directly Dated Rock Art in Southeast Asia and the Archaeological Implications - Jalandoni, Andrea (Archīum Ateneo, 2021)
This paper integrates the first rock art directly dated with radiocarbon (14C) in Southeast Asia with the archaeological activity in the area and with stylistically similar rock art in the region. Peñablanca is a hotspot of archaeological research that includes the oldest dates for human remains in the Philippines. The caves in Peñablanca with known rock art were revisited and only 37.6% of the original recorded figures were found; the others are likely lost to agents of deterioration. A sample was collected from an anthropomorph and accelerator mass spectrometry (AMS) dated to 3570–3460 cal BP. The date corresponds to archaeological activity in the area and provides a more holistic view of the people inhabiting the Peñablanca caves at that time. A systematic review was used to find similar black anthropomorph motifs in Southeast Asia to identify potential connections across the region and provide a possible chronological association.